Governance and Managerial Capacity in Driving BUMDes Success: Evidence in Pesawaran Regency - Rokhma Yeni; Edo Segara Gustanto; Tubagus Hasanudin; Dame Trully Gultom (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2026)
This study examines the influence of governance quality anda managerial capacity on the success of Village-Owned Enterprises (BUMDes) in Pesawaran Regency. As community-based economy institutions, BUMDes are expected to promote local economic development through accountable governance and effective management. A quantitative surveys was conducted involving administrators and members of active BUMDes, with data collected through structured questiannaires and analyzed using descriptive statistics and Spearman Rank correlation test. The findings indicate that the succes level of BUMDes ranges form moderatally succesful to succesful. Governance quality (reflected in transparency, accountability, and participatory decision making) shosws a significant positive relationship with organizational succes. Managerial capacity, particularly in financial management, leadership, and strategic planning, also contributes significantly to improved performance and sustainability. These results demonstrate that effective governances structures and strong managerial competencies are crucial in enhnacing the resilience and long-term succes of BUMDes in supporting village economic development.